2016
DOI: 10.1134/s0021364016100106
|View full text |Cite
|
Sign up to set email alerts
|

Decays τ → (η, η')K–ντ in the extended Nambu–Jona-Lasinio model

Abstract: The decays τ → (η, η )K − ντ are described in the framework of the extended Nambu-Jona-Lasinio model. Both full and differential widths of these decays are calculated. The vector and scalar channels are considered. In the vector channels, the subprocesses with intermediate K * (892) and K * (1410) mesons play the main role. In the scalar channels, the subprocesses with intermediate K * 0 (800) and K * 0 (1430) mesons are taken into account. Scalar channels play a less important role in calculation of the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In the 1970s Volkov and collaborators showed in a series of articles [12][13][14] that excitonic condensation in slightly offstoichiometric systems leads to formation of a uniform ferromagnetic state, although the normal state does not exhibit a magnetic instability. The idea of an excitonic ferromagnet was revived at the beginning of 2000s in the context of hexaborides (section 5.1).…”
Section: Brief History Of the Weak-coupling Theory Of Excitonic Conde...mentioning
confidence: 99%
See 3 more Smart Citations
“…In the 1970s Volkov and collaborators showed in a series of articles [12][13][14] that excitonic condensation in slightly offstoichiometric systems leads to formation of a uniform ferromagnetic state, although the normal state does not exhibit a magnetic instability. The idea of an excitonic ferromagnet was revived at the beginning of 2000s in the context of hexaborides (section 5.1).…”
Section: Brief History Of the Weak-coupling Theory Of Excitonic Conde...mentioning
confidence: 99%
“…The classification elsewhere [11] includes only the non-magnetic polar EC states. In the mid-1970s Volkov and collaborators showed that in doped material with an unequal number of electrons and holes the ferromagnetic EC state develops characterised by simultaneous presence of finite singlet and triplet components [12][13][14].…”
Section: Weak Couplingmentioning
confidence: 99%
See 2 more Smart Citations